An autologous colonic organoid‐derived monolayer model to study immune: bacterial interactions in Crohn's disease patients. Issue 8 (1st August 2022) - Angus, Hamish CK; Urbano, Paulo CM; Laws, Gemma A; Fan, Shijun; Gadeock, Safina; Schultz, Michael; Butt, Grant; Highton, Andrew J; Kemp, Roslyn A
Abstract: Objectives: Crohn's disease (CD) initiation and pathogenesis are believed to involve an environmental trigger in a genetically susceptible person that results in an immune response against commensal gut bacteria, leading to a compromised intestinal epithelial barrier and a cycle of inflammation. However, it has been difficult to study the contribution of all factors together in a physiologically relevant model and in a heterogenous patient population. Methods: We developed an autologous colonic monolayer model that incorporated the immune response from the same donor and a commensal bacteria, Faecalibacterium prausnitzii . Two‐dimensional monolayers were grown from three‐dimensional organoids generated from intestinal biopsies, and the epithelial integrity of the epithelium was measured using transepithelial electrical resistance. We determined the effect of immune cells alone, bacteria alone and the co‐culture of immune cells and bacteria on integrity. Results: Monolayers derived from CD donors had impaired epithelial integrity compared to those from non‐inflammatory bowel disease (IBD) donors. This integrity was further impaired by culture with bacteria, but not immune cells, despite a higher frequency of inflammatory phenotype peripheral T cells in CD donors. Variability in epithelial integrity was higher in CD donors than in non‐IBD donors. Conclusion: We have developed a new autologous model to study the complexity of CD, which allows for the comparison of the barrier properties of the colonic epithelium and the ability to study how autologous immune cells directly affect the colonic barrier and whether this is modified by luminal bacteria. This new model allows for the study of individual patients and could inform treatment decisions. Abstract : We developed an autologous model to study epithelial integrity in human Crohn's disease (CD). We cultured immune cells and the commensal bacterium, Faecalibacterium prausnitzii, with patient‐matched epithelial monolayers generated from three‐dimensional organoids derived from intestinal biopsies. We showed inherent differences in integrity in monolayers from CD patients and a further reduction upon culture with bacteria but not immune cells.